E-cigarettes and Vaping: A New Frontier in Youth Drug Prevention - Ali Al-Oudah, Ghadah; Jasim, Ameera; K. Hindi, Nada Khazal; Mohammed Malih Radhi; Qasim Abbas Khyoosh Al-Eqabi; Abd AL-Jabbar, Widad (Journal of Biomedicine and Biochemistry, 2025)
E-cigarettes and vaping are becoming huge public health problems, particularly among kids, despite their marketing as more secure options to traditional cigarettes. The surge in use amongst adolescents is attributed to attractive flavors, perceived protection, and competitive advertising, mainly to concerns about nicotine addiction and a potential gateway to regular smoking. The rise is connected to demographic elements, with varying usage patterns amongst distinct age, gender, and socioeconomic agencies. Short-term consequences encompass nicotine dependence and cognitive impairments, while long-term dangers include respiratory and cardiovascular issues. Key risk factors include peer strain, publicity of tobacco marketing, and intellectual fitness problems. Effective prevention strategies involve school-primarily based applications, community interventions, legislative measures like age restrictions and taste bans, and comprehensive public fitness campaigns. Future research ought to focus on the long-term health results and the improvement of focused prevention techniques, incorporating stricter policies and tracking of advertising practices.